O movimento estudantil na Reforma Universitária da PUC-SP e seu contraponto ao acordo MEC-USAID: uma disputa de projetos político-educacionais nos Anos de Chumbo (1969-1974) - Terini, Alexandre Gonçalves (2019)
This work places the student movement of the Pontifical Catholic University of São Paulo (PUC-SP) at the center of the issue throughout the University Reform process and during the Lead Years (1969-1974), seeking to problematize institutional narratives through the analysis of documentation and student testimonials on the intra and extramural relations of the university, dialogues, conflicts, disputes of projects between politically engaged students and the three main institutions that involve the "Puquian community": the Rectory, the São Paulo Foundation / Church Catholic and the military regime. Finally, we will seek not only to analyze the role of the student movement in the process of the University Reform of PUC-SP, but also to understand how this reform, especially the Basic Cycle of Human Sciences and Education of PUC-SP, represented a counterpoint or resistance to MEC-USAID agreement as a political-educational project for higher education. In order to do so, a bibliographical survey was made on the Internet and libraries, from documentary sources in archives and collections and from oral sources through the interview of alumni, former teachers and other teachers who continue to teach at university until then. The method of analysis involved centrally the class press (student and ecclesiastical) and Oral History. Unpublished documents were analyzed, such as PUC-SP student pamphlets found in the DEOPS Archives of the State Archives, as well as official documents of the Rectory of PUC-SP, as "Basic Studies for the Restructuring of the Pontifical Catholic University of São Paulo", and Catholic ecclesiastical documents such as articles and editorials of the newspaper O São Paulo and the Buga Document: "The Mission of the Catholic University in Latin America."